2014
DOI: 10.1142/s0219525914500143
|View full text |Cite
|
Sign up to set email alerts
|

Global Trade Imbalances: A Network Approach

Abstract: We study trade imbalances between world countries in the period 1960-2000 using a complex-network approach. We show that trade imbalances in absolute value are characterized by a hierarchical arrangement wherein few rich economies display high clustering and carry an important amount of global-trade imbalances. In contrast, trade imbalances in relative terms show a more fragmented topology, with less concentrated clustering which is particularly high for emergent economies. In addition, we find that traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Borrowing from the broad literature related to the ITN, a possible extension of this research would be to explore the determinants of the architecture of the network following traditional economic modeling 30 and null network models 31 . In addition, given the interplay and complementary of trade, migration, financial investment, and M&As flows, it would be interesting to develop a multilayer network analysis 10,18,28 . This could provide new insights on the international relations, and the movement of goods and factors of production that shape globalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrowing from the broad literature related to the ITN, a possible extension of this research would be to explore the determinants of the architecture of the network following traditional economic modeling 30 and null network models 31 . In addition, given the interplay and complementary of trade, migration, financial investment, and M&As flows, it would be interesting to develop a multilayer network analysis 10,18,28 . This could provide new insights on the international relations, and the movement of goods and factors of production that shape globalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the IMAN and the ITN are characterized by highly unbalanced bilateral flows. In the ITN, developed countries have more balanced trade relationships than developing countries 28 .…”
Section: Introductionmentioning
confidence: 99%
“…De Benedictis & Tajoli (2011) have studied the evolution of the world trade network over time and concluded that trade integration at the world level has been increasing, except in some areas. In addition, they find that trade policies play an Fagiolo (2014), Fagiolo et al (2010)). Network analysis is also applied to the identification of a core-periphery structure.…”
Section: Literature Reviewmentioning
confidence: 98%
“…More generally, the rising complexity and imbalances of the trade network, where some countries record large surpluses (China, Germany) and others large deficits (US, France) awake the debate on the need of a global coordinated adjustment plan involving all countries (see [19] and [20] for two recent network-related contributions on the global trade imbalances). By shrinking the size of the trade information matrix, the indirect measure can help each country to identify the trade partners with which negotiating prioritarily an adjustment plan to correct the imbalances.…”
Section: Indirect Trade Imbalance In Europementioning
confidence: 99%